Strategy Of Islamic Religious Education Teachers In Improving Student Religiousity At MTs Aisyiyah Binjai - Fadhilah Juliandari; Nur Afni Syakbaini; Yasirur Rahmah (Al-Ulum: Jurnal Pendidikan Islam, 2022)
The purpose of this study was to find out how the strategy of Islamic religious education teachers in improving student religiosity at MTs Aisyiyah Binjai. This research is a qualitative research. Data collection techniques in this study were observation, interviews, and documentation. The results of this study are that the task of the teacher is not only to provide learning materials, but the teacher is also a facilitator and invites students to increase students' religiosity through good examples as well.